1941 [videorecording (DVD)] - Spielberg, Steven, 1946-; Aykroyd, Dan; Beatty, Ned; Belushi, John (Universal Home Video, 1999)
This zany comedy spectacular from Steven Spielberg is set in Los Angeles just days after the attack on Pearl Harbor when the fear of a Japanese invasion threw the city into a state of pandemonium.